The Effect of Promotion Type and Price on Purchase Intention in E-Commerce - Koentary, Andi Supandi Suaid (Jurnal Psikologi, 2026)
Buying behavior is shifting from conventional methods to e-commerce, especially in the emerging adulthood age range. Therefore, e-commerce competes in providing promotions and prices with the best deals to expand their market. This study examines the effect of promotion type and price on purchase intention. An experimental study was conducted on participants aged 18-25 years old. Participants was assigned to purchase scenario with promotion type (discount and free shipping) as the within-subjects variable and price (cheap and expensive) as the between-subjects variable. Mixed ANOVA results reveal a significant effect of price on purchase intention (p < .01). Meanwhile, there is no significant effect of promotion type on purchase intention (p = .10). Moreover, there is no interaction between the variables on purchase intention (p = 0.24).